'Lactobacillus timonensis' sp. nov., a new bacterial species isolated from the human gut. (September 2017) - Afouda, P.; Fournier, P.E.; Raoult, D.; Merhej, V.
Abstract: Here, we describe the main characteristics of ' Lactobacillus timonenis ' sp. nov., strain Marseille-P3825 T (CSUR=P3825), isolated from a stool sample of a healthy Beninese woman.